Thirty-Two Years of Integrating Archaeology and Heritage Management in Belize: A Brief History of the Belize Valley Archaeological Reconnaissance (BVAR) Project’s Engagement with the Public - Julie A. Hoggarth; Jaime J. Awe; Claire E. Ebert; Rafael A. Guerra; Antonio Beardall; Tia B. Watkins; John P. Walden (Heritage, 2020)
Since its inception in 1988, the Belize Valley Archaeological Reconnaissance (BVAR) Project has had two major foci, that of cultural heritage management and archaeological research. While research has concentrated on excavation and survey, the heritage management focus of the project has included the preservation of ancient monuments, the integration of archaeology and tourism development, and cultural heritage education. In this paper, we provide a brief overview on the history of scientific investigations by the BVAR Project, highlighting the project’s dual heritage management and research goals. This background offers the basis in which to discuss the successes and challenges of the project’s efforts in cultural heritage management and public engagement, particularly in early conservation efforts, in its training and educational efforts, and its ongoing outreach activity. We emphasize the need to train Belizeans as professional archaeologists and conservators, to serve as the next generation of advocates for Belize’s heritage management. We offer some ideas on how research projects can make significant contributions to heritage education and preservation in the developing world.